Ice loads on azimuthing podded propulsors - Akinturk, A.; Jones, S. J.; Duffy, D.; Rowell, B. (2004)
The paper describes the experimental setup and presents some of the results obtained. The experimental system is designed and built to measure the loads on the blade, on the propeller shaft bearings, on the shaft, and on the whole propulsion unit (global loads). Experiments have been conducted at various headings form 0° to 180°, thrust directions (aft or forward), and advance coefficients. In the experiments, ice sheets of 60 mm thickness were used. Target flexural strength of the ice sheets was 60 kPa at the start of the experiments. During the course of the experiments, thickness, flexural, compressive and shear strength values of the ice sheets were sampled at certain time intervals in order to record the variations in the ice properties. Initial results suggest that there was an increase of the loads exerted on the podded system due to ice. The increase varies at different azimuth angles and advance velocities. NRC publication: Yes